Entrepreneurial Competencies and SME’s performance in Yobe State Nigeria - Gurin, Idris Mohammed; Shettima, Mohammed Bello; Ardo, Mohammed Abu (Indonesian Journal of Advanced Research, 2024)
This research has studied ‘Entrepreneurial Competencies and SME’s performance in Yobe State Nigeria’.  Based on facts and figures, it has been observed that an entrepreneurial competency has challenges affecting SME’s Performance. Therefore, the main objective of this study is to investigate the challenges affecting SME’s Performance in Yobe State. Three hypotheses were formulated for testing. In testing the hypotheses, the study made use of inferential statistics. Cross sectional method was used to collect data from 386 respondents out of which only 255 responded. Data analysis was done using Partial Least Square-Structural Equation Model (PLS-SEM) i.e. Pls3. The results The low performance in the country has led of to the rise in both poverty and unemployment rate. This is attributed to the fact that the SMEs are being faced with challenges relating to lack of entrepreneurial competencies. Because of this, this study, which uses data from a sample of the state's registered small and medium-sized enterprises, fills a knowledge gap by demonstrating the impact of innovation, networking, and risk-taking competencies on SME success.